Formulating a Health Sustainable Development Policy: How the Actors Handling the COVID-19 in Indonesia - Novia Amirah Azmi; Annisa Weriframayeni; Retno Dewi Pramodia Ahsani; Delila Putri Sadayi; Aqil Teguh Fathani (Universitas Teuku Umar, 2021)
This article aims to analyze the role of actors in COVID-19 control in Indonesia and identify sustainable development policies in the health sector. The significant impact of COVID-19 occurs in the health sector, so the critical primary role of the government is to formulate policies in the health sector to control COVID-19. This research used a descriptive qualitative method by analyzing the policies made and the role of actors in covid-19 control in the field of health. This research data uses secondary data from national and international journal articles, government websites, and national online media news during the COVID-19 pandemic. The technique of analyzing research data uses Vosviewer and Nvivo 12 plus software so that data visualization can be presented as a basis for formulating health development policies and how the role of actors in controlling COVID-19. This study indicates, 1) the pattern of health development policies in controlling COVID-19 still needs improvement in effectiveness and efficiency so that policies are right on target. 2) policies made in controlling COVID-19 in Indonesia are still not optimal, especially in integrating technology and other resources. 3) the government is not ready to control COVID-19; the role of other actors is still low in intensity in controlling COVID-19. Based on the research analysis it is important to formulate policies to control COVID-19 and identify its role. Thus, this research can provide a reference in formulating sustainable policies in controlling COVID-19 in the health sector.